Wind Speed and Direction Estimation from Radar SAR using Sentinel -1, in the Cyprus region - Kalogirou, Eleftheria; Melillos, George; Hadjimitsis, Diofantos G. (My University, 2023)
Wind data can be valuable in several ways for maritime surveillance, including vessel behavior. Wind speed and direction can affect the speed, direction, and maneuverability of ships. By analyzing wind data, it is possible to understand how vessels may be affected by the wind, which can help in predicting their paths and possible destinations. Pollution tracking, in the event of an oil spill or other pollutant release, wind data can help predict the movement and dispersion of the pollutant. This information can be critical in emergency response and containment efforts. Also, the weather and sea state forecasting, wind data is an important input for forecasting weather and sea conditions. Knowing the expected wind speed and direction can help mariners plan safe routes and avoid areas of potentially hazardous conditions. Wind data can help identify areas where persons or vessels may be drifting or stranded due to wind-driven currents or other effects. In general, wind data can provide valuable information to maritime surveillance efforts, helping to improve safety, security, and environmental protection. The paper aims to analyze wind data in the Cyprus region, during the day using Sentinel-1 data. The analysis of the data it became with the software SNAP and QGIS. The preliminary results show that both tools can be used for wind data analysis and give satisfactory results.
Keywords: Cyprus; SAR; Sentinel-1; Wind Direction; Wind Speed